2017
DOI: 10.1038/s41598-017-09904-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Delivery System Based on Salmon DNA Nano- and Micro-Scale Structures

Abstract: Microneedles, fabricated by nano-moulding technology show great promise in the field of drug delivery by enabling the painless self-administration of drugs in a patient-friendly manner. In this study, double-stranded salmon DNA (SDNA) was used as both a drug-delivery vehicle and structural material with a microneedle system. SDNA is non-toxic and demonstrates good mechanical robustness, mouldability, biocompatibility, bio-absorbability, and binding affinity with drug molecules for bio-functional applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…PDMS (Sylgard 184; Dow Corning, Midland, MI, USA) prepared by mixing elastomer and curing agent in a ratio of 10: 1 was poured onto a master stamp. The molds were cured at 50 °C for 2 h. The PDMS mold was then separated from the stamp 10,11,42 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PDMS (Sylgard 184; Dow Corning, Midland, MI, USA) prepared by mixing elastomer and curing agent in a ratio of 10: 1 was poured onto a master stamp. The molds were cured at 50 °C for 2 h. The PDMS mold was then separated from the stamp 10,11,42 .…”
Section: Methodsmentioning
confidence: 99%
“…It can effectively deliver drugs or active ingredients to the skin by crossing over the stratum corneum [5][6][7][8][9][10][11] . Among the various types of microneedles [5][6][7][8][9][10][11] , dissolving microneedles are made of a water-soluble polymer that exhibits excellent biocompatibility. The dissolving microneedles penetrate the skin and get dissolved by the fluid in the skin to deliver drugs or effective ingredients 8,10,11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The high loading capacity of the drugs and topical application provided strong support for in vivo therapeutic outcomes while minimizing the side effects [70]. interactions between DNA molecule and DOX, which made it a stable vehicle for drug delivery [80]. There are various materials used to develop MNs to explore release kinetics and skin diffusion of anticancer drugs such as dacarbazine [81], doxorubicin [73,78,82] and MTX [31,72].…”
Section: Chemotherapymentioning
confidence: 99%
“…The biomedical use of DNA in regenerative medicine has also been prominent in recent years 2,4,10 . However, much of the effort focused mainly on the development of DNA nanostructures as drug delivery systems due to the lowest antigenicity of DNA as compared to other macromolecules and the ability of cytokines to be stacked between DNA bases 5,6,12‐14 . Our group's studies have demonstrated the high biocompatibility and excellent controlled drug release properties of DNA‐based polymeric adhesive films 7,9 .…”
Section: Introductionmentioning
confidence: 99%